THEORETICALLY POSSIBLE AND PRACTICALLY RELIZABLE PRODUCTIVITY OF THE LIGHT-CHESTNUT SOILS OF THE NORTHERN WEST PRECASPIAN REGION ACORDING TO THE MOISTURE AND SOLINITY (ON EXAMPLE OF KOCHUBEY BIOSPHERE STATION OF PIBR DNC RAS) - G. N. Hasanov; T. A. Asvarova; K. M. Gadzhiev; Z. N. Akhmedova; A. S. Abdulaeva; R. R. Bashirov; M. S. Sultanakhmedov (Юг России: экология, развитие, 2014)
Abstract. The article presents the productivity data, the species composition and utilization rates phytocenoses FAR depending on theintegrals of dryness and moisture climate volatility, coefficient of moisture and dynamics of harmful salts in the soil according to years and seasons of the year.Methods.The studies were conducted on light-chestnut carbonate saline soil of Kochubey biosphere stations on the territory of the Terek- Kuma Lowland Precaspianregion in 2011–2013. The calculation of the use of FAR was conducted using the formula A.A. Nichiporovich to determine the theoretically possible yield of plants. Klimatogrammy during these years has been compiled by the method Walter. Stocks above and below ground plant matter into account by the method of A.A.Titlyanova.The names of species given by S.K. Cherepanov.Results. According to the results of our observations, the most important for achieving high productivity ephemeral synusia under these conditions include precipitation for April and May. Between the amount of rainfall in April and May and the productivity of abovegroundphytomass ofephemera direct correlation exists, which in 2011 had a strong, and in the next two years-the average severity. In 2012 the volatility increased, KU fell in 5 times. Such weather conditions contributed to the rise of water-soluble salts to the upper soil horizons and substantial change in species composition phytocenoses. The content Cl- in the layer 0–20 cm over the same period 2011 increased in 3.9 times, SO4--- 1.7 in times. If in 2011 the stepen soil salinity in the layer 0–35 cm characterized as weak, in 2012 the average at the same chloride- sulphate type of salinity. Obviously , an increase in the content of Cl- - ions and its relationship to the S04-- contributed to a dramatic increase in productivity and thistle herbs in 2012. Luxuriant growth of Salsola iberica Sennen et Pau particularly stood.Thus, the formation of a biomass and species composition in the Terek-Kuma Lowland Precaspian is the result of the cumulative effects of different environmental factors, the main ones are: precipitation, air temperature, its relative humidity, evaporation, moisture ratio and the degree of soil salinity and chemistry. These dependencies are expressed by the following multiple regression equation. Depending on climatic conditions, the pasture use phytocoenoses 0,20–0,57 % FAR. Win ephemera and ephemeroids of this amount is an average over years of research about 20 %, the remaining 80%-grasses and thistle, the majority of which occur in Salsola iberica Sennen et Pau, bad eating animals and less valuable as fodder representative thistle. Main conclusion.Our results suggest that, in the context of the Terek-Kuma Lowland there are two peaks of productivity of phytocenoses: first one of ephemeras andephemeroids is in mid-May to early July, the second one of grasses and thistleis in the second half of September. The main factors to achieve high productivity ephemeras and ephemeroids on light-chestnut soil of the North- West Precaspian are about 80–85 mm rainfall during April – May, with average daily air temperature 15–16 °C, its relative humidity 70–73 %, volatility of 130–140 mm, KU 0.30, chloride-sulphate type of salinity in the layer of a low degree of 0–35 cm. In years with heavy rainfall in July and August (102 mm), despite an increase in average daily air temperature to 25–26 °C and volatility to 275mm, a relatively high KU (0.21), the content of Cl-in the layer 0–20 cm reduced 1,40 mg-ekv./100 g, ratio Cl-:SO4-- to 0,59–0,84 and productivity grasses and Salsola iberica Sennen et Pauincreased. The FAR utilization reaches 0.57, of which the biomass of grasses and Salsola iberica Sennenet Pau falls 87.6 % (2012).The task of future research is to determine its phitomeliorative role: removal of salt-forming ions from the soil and itsfurther redistribution in ecosystem, considering the nature of movement on the territory of Salsola iberica Sennen et Pau.